Ptilodactyla exotica Chapin, 1927 in Italy (Coleoptera: Ptilodactylidae) - Nardi, Gianluca; Bocci, Maura; Poggi, Roberto (Zootaxa, 2020)
Ptilodactyla exotica Chapin, 1927 is a subcosmopolitan synanthropic species introduced to Europe with tropical ornamental plants. It is here firstly recorded from central Italy (Tuscany region), and its Italian chronogeonemy (1940–2016) is summarized. Most records come from the Genoa province (Northern Italy, Liguria region), where this species was repeatedly collected in the period 1940–1999.